Novel Herbal Gel of Kigelia africana (Lam.) Benth, Fruits Extract Formulation and Evaluation - Bhramaramba, R.; Babu, A. Narendra; Kumar, T. Nagendra (Pharmaceutical Science: New Insights and Developments Vol. 5, 2025)
The whole plant of Kigelia africana (Lam.) Benth. belongs to the Bignoniaceae family and is widely cultivated throughout tropical and subtropical regions of the world, mainly in India and South Africa. Herbal medicine has gained significant global importance due to its medicinal properties and economic value. These herbal medicines have increased; their quality, safety, and efficiency are serious concerns in industrialized and developing countries. The kigelia plant is easily available at river banks and woodlands. The present research has been undertaken with the aim of formulating and evaluating the herbal gel containing Kigelia africana (Lam.) Benth., fruit extract. The Kigelia africana (Lam.) Benth., fruit extract contains Alkaloids, Saponins, Glycosides, Carbohydrates, Tannins, Flavonoids, Proteins, Terpenoids, and Fats. The gel formulation was developed by using Carbopol 940, Kigelia africana (Lam.) Benth., fruit extract, propylene glycol, methyl paraben, propyl paraben, and the required amount of distilled water. The skin pH (6.8-7.1) was maintained by dropwise addition of Triethanolamine. The physicochemical Parameters of formulations (pH, spreadability, Stability, etc.) were determined. Stability studies have been carried out as per ICH guidelines for 3 months at different temperatures and humidity. The results showed that the formulation containing 5% Kigelia africana (Lam.) Benth., fruit extract shows better stability. Further formulations have been studied for skin irritation on the animal model (Rat), and results showed that there was no skin irritation in animals. In conclusion, the studies revealed that the developed single herbal formulation consisting of 5% Kigelia africana (Lam.) Benth., extract comparatively better than the other formulations, but all the formulations were non-irritant and did not show any skin toxicity when applied daily for 7 days in rats. Its antibacterial and antifungal property was not under taken for any scientific study with herbal gel.